Investigating Possible Gastroliths in a Referred Specimen of Bohaiornis guoi (Aves: Enantiornithes) - Liu, Shumin; Li, Zhiheng; Bailleul, Alida M.; Wang, Min; O’Connor, Jingmai (Frontiers in Earth Science, 2021)
Gastroliths, where preserved, can provide indirect evidence regarding diet in extinct avian and non-avian dinosaurs. Masses of gastroliths consistent with the presence of a gastric mill are preserved in many Early Cretaceous Jehol birds mostly belonging to the Ornithuromorpha. Gastroliths are also present in basal birds Sapeornis and Jeholornis in which herbivory is supported by direct evidence these taxa consumed seeds in the form of crop or stomach contents. Although gastroliths have been correlated with herbivory in non-avian dinosaurs, the presence of gastroliths and bone together in Ambopteryx calls this association in to question. Despite being known from greater numbers of specimens than other avian lineages, no unequivocal direct or indirect evidence of diet has been recovered from Jehol deposits for the Enantiornithes. A referred specimen of Bohaiornis guoi IVPP V17963 was described as preserving a small number of gastroliths interpreted as rangle, gastroliths whose function is cleaning the stomach in extant raptorial birds. However, based on comparison with gastroliths in other Jehol birds, it has alternatively been suggested that the identified structures are not ingested stones at all but some unusual mineral precipitate. Considering the limited evidence regarding diet in Enantiornithes and the importance of accurately identifying the traces in Bohaiornis in order to understand the enantiornithine digestive system, we extracted two samples of these purported gastroliths and explored these traces using computerized laminography scanning, scanning electron microscopy, energy dispersive x-ray spectroscopy, ground sections, and body size to gastral mass regressions. Similar analyses were conducted on gastroliths extracted from undisputed gastral masses of two Jehol ornithuromorphs and the non-avian pennaraptoran Caudipteryx. The combined results contradict the hypothesis that these traces are gastroliths and supports the interpretation they are mineral precipitate, most likely authigenic quartz (chalcedony). Although authigenesis is commonly responsible for the preservation of soft tissues, it is unclear if these traces record part of the tissues of this Bohaiornis. This study highlights the importance of a multidisciplinary approach in understanding unusual traces in the fossil record and reveal a previously unidentified taphonomic phenomenon in fossils from Jehol deposits.